Ownership Structure and Publicness of Firms: A Literature Review - Untoro, Wisnu (University of Merdeka Malang, 2017)
There has been an extensive body of literature studying the link between ownership structure and firm performance. Some of them focus on the performance difference across ownership types (i.e. state vs foreign vs private domestic). On the other hand, some studies stress ownership structure on the fraction of ownership based on agency theory (i.e. majority versus minority) and its derivatives (e.g. ultimate ownership, cross-listing). However, an important element has not been explored while discussing the ownership structure of firms which is the concept of the publicness of firms. Publicness is important to explain to which extent an organization is related to governmental institutions. In fact, there are many engagements of firms with governmental bodies (e.g. deposit and lending from and to the public organization). In this present paper, I provide a comprehensive literature review on the intersection between the publicness level of firms and ownership structure. Going deeper, I also provide a literature review on the measurement of publicness and postulate a model to link between these two and firm performance as a venue for future studies.DOI: https://doi.org/10.26905/jkdp.v21i4.1560